Persepsi Karyawan Mengenai Pengaruh Efektifitas Pengendalian Internal, Ketaatan Aturan Akuntansi Dan Kesesuaian Kompensansi Terhadap Kecurangan - Marlina, Nurlenni Astuti; Rifa’i, Ahmad; Surasni, Ni Ketut (E-Jurnal Akuntansi, 2019)
The purpose of the study was to determine employee perceptions regarding the effect of the  effectiveness of internal controls, compliance with accounting rules and conformity of  compensation to fraudulent tendencies at PT. NTB Syariah Bank in the West Nusa Tenggara  region. The dependent variable used in this study is fraudulent tendencies. The independent  variable used in this study is the effectiveness of internal controls, compliance with accounting   rules and conformity of compensation. This study uses employee respondents who are directly  related to banking transactions, especially in the operational part of 50 people randomly  selected. Method Analysis of the data used is multiple linear regression. The results of the  analysis show the effectiveness of internal controls and suitability of compensation does not  affect fraudulent tendencies at PT. NTB Syariah Bank. Whereas compliance with accounting rules has an influence on fraudulent tendencies. Keywords: Fraud, internal control, compliance, compensation.